The Reflection of International Standards for Ensuring the Right to Freedom and Personal Security in Current Vietnamese Criminal Procedure Code - Nguyen, Thi Kim Cuc (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
The right to freedom and personal security is a fundamental human right that can be found in a plethora of international and regional instruments. Firstly, this right is enshrined in the Universal Declaration of Human Rights, as articulated in Article 3, which states that everyone has the right to liberty and security of person. Additionally, other treaties have acknowledged the right to freedom and personal security, including but not limited to the ASEAN Human Rights Declaration and the International Covenant on Civil and Political Rights. In addition to the principle of equality, freedom and personal security are widely regarded as values of democracy, and contemporary Vietnamese society has the task of effectively reconciling and striking a balance between these three elements in a rational manner. This article aims to examine Vietnam’s implementation of the commitment to ensure the right to freedom and personal security in human rights treaties to which it is a member. This implementation originated from the principle of pacta sunt servanda, which states that governments have a responsibility to comply with international treaties. Using the analysis and synthesis method, this article focuses on studying international standards that guarantee the right to freedom and personal security, as well as the relevant provisions of the current Vietnamese Criminal Procedure Code. This study employs a comparative method to illustrate how the current Vietnamese Criminal Procedure Code reflects international standards for the right to freedom and personal security. As a result, some findings and initial discussions are highlighted to enhance the effective implementation of ensuring and enhancing the right to freedom and personal security, with the aim of building a rule-of-law state.